Towards Optimal Business Regulatory Governance in India Report of the Working Group on Business Regulatory Framework 2011 Steering Committee on Industry - Planning Commission (Planning Commission, 2011)
Planning plays an important role in determining optimal utilisation of resources, both human and material, for realising the desired growth and development trajectory of any country. Since its independence, India has resorted to a robust government lead planning process that engages scholars, development practitioners, businesses and various stakeholders to evolve a collective approach accompanied with specific actions and targets for the ensuing years. At this juncture, the Planning Commission of India is in the process of developing the Twelfth Five Year Plan (XII FYP) for the country. It has formed a Steering Committee on Industry to deliberate upon the ways and means of creating an enabling business ecosystem for sustainable and inclusive business development in the country. In this endeavour, such alternatives are being explored that could boost industrial performance in general and manufacturing sector performance in particular.
Planning Commission Government of India
Planning Commission Government of India